Characterization of key aroma compounds in flat peach juice based on gas chromatography-mass spectrometry-olfactometry (GC-MS-O), odor activity value (OAV), aroma recombination, and omission experiments. (1st January 2022) - Tan, Fengling; Wang, Peng; Zhan, Ping; Tian, Honglei
Graphical abstract: Highlights: Aroma profiles of fresh flat peach juice (FPJ) samples were characterized by GC-MS-O. 32 aroma-active compounds were identified and 14 aroma-active compounds with OAVs > 1. Positive correlation between key aroma-active compounds and sensory properties. 14 key aroma compounds contributed greatly to the overall aroma of FPJ samples. Abstract: The aroma profiles of fresh flat peach juice (FPJ) samples obtained from four different cultivars (RP1), (ZLP), (RP18), and (ZP) were characterized by gas chromatography-Mass spectrometry-olfactometry (GC-MS-O). Totally, 32 aroma-active compounds in FPJs were identified by GC-MS-O and further quantified. Of these, 14 aroma-active compounds presented odor activity values (OAVs) greater than 1, with several lactones and aldehydes contributing as key aroma-active components of FPJs. Partial least-squares regression (PLSR) revealed that RP18 was greatly related to "fruity", "sweet" and "peach-like" attributes, while ZLP was highly correlated with "floral" and "green and grassy" attributes, confirming the quantitative describe analysis (QDA) results. In addition, an aroma recombination experiment was conducted to mimic the aroma profile of flat peach juice based on the actual concentrations of RP18. Omission experiments indicated that lactones were very highly significant for the characteristic aroma of FPJ.